The light in the forest - Richter, Conrad, 1890-1968 (New York : Bantam Books, 1990)
Four-year-old John Butler is captured by the Delaware Indians and is adopted by one of the tribes leaders. Suddenly, after 11 years among the Delaware people, he is forced to return to his original home and parents by the Boquet military expedition of 1765. But his deep love for and loyalty to his Indian parents and his cousin Half Arrow, is his reason for rejecting the white man's civilization
"A Bantam starfire book."
Keywords: Juvcol; Children's literature